COMPACTIFICATIONS OF SUBSCHEMES OF INTEGRAL MODELS OF SHIMURA VARIETIES. (24th September 2018) - LAN, KAI-WEN; STROH, BENOÎT
Abstract : We study several kinds of subschemes of mixed characteristic models of Shimura varieties which admit good (partial) toroidal and minimal compactifications, with familiar boundary stratifications and formal local structures, as if they were Shimura varieties in characteristic zero. We also generalize Koecher's principle and the relative vanishing of subcanonical extensions for coherent sheaves, and Pink's and Morel's formulas for étale sheaves, to the context of such subschemes.